In league? Destination marketing organisations and football clubs in the virtual space. Issue 4 (2nd October 2018) - Proctor, David; Dunne, Gerard; Flanagan, Sheila
ABSTRACT: Logic dictates that destination marketing organisations (DMOs), while representing many stakeholders, should leverage a location's most visible assets to enhance the attractiveness of the destination at any given opportunity. This study examines the manner and extent to which four major European football franchises are mentioned and promoted on the official digital marketing platforms of their respective cities; Amsterdam, Barcelona, Manchester and Munich. A tailor-made content analysis tool is used to conduct a systematic investigation of the virtual platforms over which the DMOs of these cities exert a modicum of control. The content of these platforms is scrutinised from three perspectives; promotional, information dissemination or push towards purchase via external links. The four cities forming part of this study are home to some of the world's most iconic global sporting brands. The research uncovers a level of confusion or simple lack of know-how on the part of DMOs as to how these hugely popular clubs can or should be exploited in the digital space. It proffers solutions to this dilemma as in initiating cooperative marketing efforts between the respective organisations and exposes a contemporary field that necessitates further research.